Validation of a translated Chinese version of the Participation Strategies Self-Efficacy Scale: a cross-sectional study. Issue 18 (28th August 2022) - Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Zhao, Jie; Choi, Kai Chow; Lam, Simon Kwun Yu; Saran, Ravneet; Shi, Jinping; Thompson, David R.; Lau, Alexander Yuk Lun
Abstract: Purpose: To examine the psychometric properties of a Chinese version of the Participation Strategies Self-Efficacy Scale (PS-SES) among stroke survivors. Methods: The PS-SES was translated into Chinese. A cross-sectional descriptive study was conducted with 336 stroke survivors recruited from the neurology departments of five hospitals in China. Reliability, concurrent validity, and construct validity of the scale were determined. Results: The Chinese version of the PS-SES (PS-SES-C) showed good internal consistency and test–retest reliability, with a Cronbach's α of 0.98 and an intraclass correlation coefficient of 0.79. There was a moderate to strong positive correlation between the PS-SES-C and Chinese version of the General Self-Efficacy Scale ( r  = 0.59, p  < .001), positive correlations between the PS-SES-C and Chinese versions of the Modified Barthel Index ( r  = 0.59, p  < .001), Rivermead Mobility Index ( r  = 0.70, p  < .001), and Reintegration to Normal Living Index ( r  = 0.70, p  < .001), and a negative correlation between the PS-SES-C and National Institutes of Health Stroke Scale ( r = −0.63, p  < .001). Known-group validity and factorial validity were also supported. Conclusions: The PS-SES-C is a reliable and valid instrument for assessing self-efficacy in managing the participation of Chinese stroke survivors. Implications for rehabilitation: Self-efficacy significantly predicts activity and participation in stroke survivors and is a major outcome measure in many stroke rehabilitation programmes. The translated Chinese version of the Participation Strategies Self-efficacy Scale is a valid and reliable tool to evaluate stroke survivors' self-efficacy in managing participation. The Chinese version of the Participation Strategies Self-efficacy Scale can be used to assess stroke recovery among the Chinese population in clinical and research settings.